Law and Policy as Tools in Healthy People 2030. (13th November 2021) - Teitelbaum, Joel; McGowan, Angela K.; Richmond, Therese S.; Kleinman, Dushanka V.; Pronk, Nico; Ochiai, Emmeline; Blakey, Carter; Brewer, Karen H.
Abstract : Laws and policies are critical determinants of health and well-being. They can encourage positive behaviors and discourage harmful behaviors, and they can enhance or worsen health, health equity, health disparities, and health literacy. Recognizing their contribution to conditions in the environments in which people are born, live, learn, work, play, worship, and age, and people's experiences of these conditions, the US Department of Health and Human Services considered the roles of law and policy throughout its development of Healthy People 2030. Laws and policies often interrelate, but they have different purposes. A law is an established procedure, standard, or system of rules that members of a society must follow. A policy is a decision or set of decisions meant to address a long-term purpose or problem. Healthy People 2030 offers an opportunity for users in diverse sectors and at all levels to use laws and policies to support or inform the initiative's implementation, address health disparities and health inequities, and improve health and well-being in this decade. Introducing new laws and policies or rescinding existing ones to achieve Healthy People 2030 goals offers a chance to rigorously assess outcomes and weigh the balance of good outcomes against unintended consequences.